ON HORIZONTAL BIHARMONIC CURVES IN THE HEISENBERG GROUP Heis3 - Korpinar, Talat; Turhan, Essin (Springer Heidelberg, 2010)
In this paper, we study non-geodesic biharmonic curves in the Heisenberg group Heis(3). We prove that there exist no non-geodesic horizontal biharmonic curves in the Heisenberg group Heis(3).
Keywords: Heisenberg group; biharmonic curve; horizontal curve